Hesperetin alleviates the inhibitory effects of high glucose on the osteoblastic differentiation of periodontal ligament stem cells. - So Yeon Kim; Jin-Yong Lee; Yong-Duk Park; Kyung Lhi Kang; Jeong-Chae Lee; Jung Sun Heo (PLoS ONE, 2013)
Hesperetin (3',5,7-trihydroxy-4-methoxyflavanone) is a metabolite of hesperidin (hesperetin-7-O-rutinoside), which belongs to the flavanone subgroup and is found mainly in citrus fruits. Hesperetin has been reported to be an effective osteoinductive compound in various in vivo and in vitro models. However, how hesperetin effects osteogenic differentiation is not fully understood. In this study, we investigated the capacity of hesperetin to stimulate the osteogenic differentiation of periodontal ligament stem cells (PDLSCs) and to relieve the anti-osteogenic effect of high glucose. Osteogenesis of PDLSCs was assessed by measurement of alkaline phosphatase (ALP) activity, and evaluation of the mRNA expression of ALP, runt-related gene 2 (Runx2), osterix (OSX), and FRA1 as osteogenic transcription factors, as well as assessment of protein expression of osteopontin (OPN) and collagen type IA (COLIA). When PDLSCs were exposed to a high concentration (30 mM) of glucose, osteogenic activity decreased compared to control cells. Hesperetin significantly increased ALP activity at doses of 1, 10, and 100 µM. Pretreatment of cells with hesperetin alleviated the high-glucose-induced suppression of the osteogenic activity of PDLSCs. Hesperetin scavenged intracellular reactive oxygen species (ROS) produced under high glucose condition. Furthermore, hesperetin increased the activity of the PI3K/Akt and β-catenin pathways. Consistent with this, blockage of Akt or β-catenin diminished the protective effect of hesperetin against high glucose-inhibited osteogenic differentiation. Collectively, our results suggest that hesperetin alleviates the high glucose-mediated suppression of osteogenic differentiation in PDLSCs by regulating ROS levels and the PI3K/Akt and β-catenin signaling pathways.